Consumer Preferences for Gender Representation in Business Names in Balongbendo District: A Sociolinguistic Study - Wahyu Ramadan, Mochammad; Imawati, Endah (Journal of Indonesian Literacy and Indigenous Culture, 2025)
This study aims to describe consumer preferences for gender representation in business names in Balongbendo sub-district. The sociolinguistic approach is used in this study to examine the sociological relationship between society and language use, which in this study is related to the selection of business names. This type of research is qualitative-descriptive, with data collection methods in the form of observation and interview methods. After the data is collected, it is analyzed using a content analysis technique. The results of this study show that 1) people’s perceptions of business names are generally influenced by various factors such as the strength of branding, personal relationships with business owners, visual appearance of banners, and the types of products offered. 2) Gender representation in business names is interpreted by the community as a reflection of certain social identities and values. Women’s names in business are associated with warmth, authenticity, and domestic skills, while men’s names are perceived as neutral, professional, and able to reach a wider consumer segment. 3) The influence of gender representation on consumer preferences shows the existence of social segmentation in purchasing decisions.